Sex Identification of Beautiful Birds from Feathers by PCR Method - Khimmakthong, Umaporn; Kraithep, Kittikorn; Muadthongon, Panik (Recent Science and Technology, 2025)
PCR is an accurate and effective method for sex identification of young birds. However, extracting DNA from birds' blood samples can cause stress and injury to the birds. Using feathers instead of blood for DNA extraction is a more convenient and safer alternative for birds. When comparing DNA extraction from blood and chicken feathers, DNA from feathers was found to be as effective as that from blood in amplifying DNA using PCR. Sex identification was performed by extracting DNA from their feathers and used two pairs of primers, P2-P8 and 2550F-2718R, specific to the CHD gene in birds, with the 18s rRNA gene primer as a control. The results showed that the P2-P8 primer pair could only be used to identify the sexes of Sun Conure parrots. Female sun conures have a DNA band of approximately 350 base pairs corresponding to the CHD gene. The 2550F-2718R primer pair can be used to identify the sexes of both Sun Conures and Green Cheek Normal parrots. The female Sun Conure parrot has a DNA band of the CHD gene measuring approximately 650 base pairs, and the female Green Cheek Normal parrot has a DNA band of the CHD gene measuring approximately 450 base pairs.